The function of innovvative technologies in the process of forming of reflection culture of teachers of preschool educational establishments (Pedagogy of Higher and Secondary Education, 2013)
Kondratec I. V. The function of innovvative technologies in the process of forming of reflection culture of teachers of preschool educational establishments.The article is devoted the problem of forming  of reflection culture for the teachers of preschool educational establishments in the conditions of  introduction of innovative technologies. The analysis of the modern state of problem is carried out, essence and methods of forming  of reflection is specified for teachers,  methods and receptions which are instrumental in effective development of reflection abilities and skills.
Keywords: reflection; reflection culture; reflection environment; reflection abilities and skills; innovative technologies